Habits and orders of everyday life: commensal adjustment in Anglo‐French couples. (17th April 2018) - Darmon, Isabelle; Warde, Alan
Abstract: This paper examines processes of habit reshuffling and change in different contexts of household formation, looking specifically at habits regarding eating and commensality. It is based on a study of 14 couples, each with one English and one French partner, half of whom live in France, half in England. We examine the interplay between partners, their determination to eat together as a couple, and the various 'orders' associated with their commensal pact (diets, routines, extra‐marital commensality), both when they start as couples and as parents of young children. We draw on the specificity of cross‐national couple experience to cast light on processes of adjustment – to one another, and to the new country of residence for the migrant partner. In particular, we explore the potential of notions of 'split' and 'solid' 'patrimonies of incorporated habits', 're‐shuffling' of habits and dispositions, and 'habit memory', to characterize the dynamics of habits at play in each of the orders under scrutiny. Overall, the paper contributes to the analysis of habit as the 'stuff' of orders of everyday life.